Effect of 0.02% and 0.01% atropine on ocular biometrics: A two-year clinical trial - Wang, Ming; Cui, Can; Yu, Shi-Ao; Liang, Ling-ling; Ma, Jing-Xue; Fu, Ai-Cun (Frontiers in Pediatrics, 2023)
Abstract Purpose Several studies have shown that some concentrations of low-concentration atropine can reduce myopia progression and control axial elongation safely and efficiently in children. The aim of this study was to evaluate the security and effects of 0.02% and 0.01% atropine on ocular biometrics. Methods Cohort study. 138 and 142 children were randomized to use either 0.02% or 0.01% atropine eye drops, respectively. They wore single-vision (SV) spectacles, with one drop of atropine applied to both eyes nightly. Controls (N=120) wore only SV spectacles. Ocular and corneal astigmatism were calculated using Thibos vector analysis and split into J0 and J45. Results The changes in cycloplegia spherical equivalent refraction (SER) and AL were -0.81±0.52D, -0.94±0.59D, and -1.33±0.72D; and 0.62±0.29mm, 0.72±0.31mm, and 0.89±0.35mm in the 0.02% and 0.01% atropine and control groups, respectively (all P<0.05). The anterior chamber depth (ACD) and ocular astigmatism (including J0) increased, and lens power decreased in the three groups (all P<0.05). However, there was no difference in the changes among them (all P>0.05). Intraocular pressure (IOP), corneal curvature, ocular astigmatism J45, and corneal astigmatism (including J0 and J45) remained stable over time in the three groups (all P>0.05). The contributions to SER progression from the changes in AL, lens and corneal power of the three groups were similar (P>0.05). The contribution of AL change alone to the change in SER was 56.3%, 63.4% and 78.2% in the above corresponding three groups. Conclusions After 2 years, 0.02% and 0.01% atropine had no clinical effects on corneal and lens power, ocular and corneal astigmatism, ACD or IOP compared to the control group. 0.02% and 0.01% atropine helped to control myopia progression mainly by reducing AL elongation.